Search for new physics in events with two soft oppositely charged leptons and missing transverse momentum in proton-proton collisions at root s=13 TeV - Sirunyan, A. M. (2018)
A search is presented for new physics in events with two low-momentum, oppositely charged leptons (electrons or muons) and missing transverse momentum in proton-proton collisions at a centre-of-mass energy of 13TeV. The data collected using the CMS detector at the LHC correspond to an integrated luminosity of 35.9 fb(-1). The observed event yields are consistent with the expectations from the standard model. The results are interpreted in terms of pair production of charginos and neutralinos ((chi) over tilde (+/-)(1) and (chi) over tilde (0)(2)) with nearly degenerate masses, as expected in natural supersymmetry models with light higgsinos, as well as in terms of the pair production of top squarks ((t) over tilde), when the lightest neutralino and the top squark have similar masses. At 95% confidence level, wino-like (chi) over tilde (+/-)(1)/(chi) over tilde (0)(2) masses are excluded up to 230GeVfor a mass difference of 20GeV relative to the lightest neutralino. In the higgsino-like model, masses are excluded up to 168GeV for the same mass difference. For (t) over tilde pair production, top squark masses up to 450GeVare excluded for a mass difference of 40GeV relative to the lightest neutralino. (C) 2018 The Author(s). Published by Elsevier B.V.